Integrative multi-omics and bioinformatics analysis of the effects of BaiRui YuPingFeng Powder on intestinal health in broilers - Xu, Haonan; Zhang, Fang; Che, Yan; Cui, Yu; Yao, Qisheng; Guan, Yueqin; Chen, Hao; Huang, Yuying (Frontiers in Veterinary Science, 2025)
IntroductionIn recent years, global poultry consumption has increased rapidly, making chicken the most widely consumed meat worldwide by 2019. To increase livestock development, antibiotics are often added to animal feed as growth promoters. But overuse of antibiotics may alter the gut microbiota, make people more resistant to them, and raise the possibility that they will spread antibiotic resistance genes to the human microbiome. Therefore, identifying safe and effective alternatives to antibiotics in livestock production is crucial for maintaining and improving gut microbial balance, ultimately promoting poultry health. The aim of this study was to investigate the mechanisms behind the impacts of BaiRui YuPingFeng Powder (TCYP) on intestinal health in broilers using combined metabolomics, bioinformatics analysis, and 16S rRNA sequencing.MethodsIn a 42-day feeding trial, 300 one-day-old broilers were randomly divided into five groups (six replicates per group; 10 broilers per replicate) fed a basal diet with or without supplements: control (CON), antibiotic (ATB), and TCYP at 500, 1000, and 1500 mg/kg. Growth performance, serum biochemical parameters, intestinal morphology, cecal microbiota composition, and metabolomic profiles were analyzed. Bioinformatics analysis was used to identify potential targets and pathways, followed by qPCR validation of key genes.ResultsCompared with the CON group, TCYP administration dose-dependently reduced the feed-to-gain ratio (F/G) and average daily feed intake (ADFI) while increasing average daily gain (ADG), with the high-dose TCYP showing more pronounced effects (p < 0.05). Serum biochemical analysis revealed that TCYP treatment significantly decreased serum levels of total cholesterol (T-CHO), triglycerides (TG), lactate dehydrogenase (LDH), and alanine aminotransferase (ALT) in a dose-dependent manner, while elevating albumin (ALB) content. These beneficial effects were particularly marked in the high-dose TCYP group (p < 0.05). Histopathological examination indicated that high-dose TCYP significantly enhanced villus height and the villus-to-crypt ratio (V/C) in the duodenum, jejunum, and ileum compared to the CON group (p < 0.05). 16S rRNA sequencing analysis revealed that TCYP treatment significantly modified the β-diversity of cecal microbiota (p < 0.01). Compared to the CON group, ATB treatment increased the abundance of Faecalibacterium and Lachnospiraceae_unclassified but reduced Ruminococcaceae_unclassified and Firmicutes_unclassified. Notably, dietary TCYP supplementation maintained gut microbiota profiles similar to the CON group, demonstrating its stabilizing effect on microbial community structure in broilers. Metabolomic analysis identified differential metabolites primarily involved in lipid and lipid-like molecules, organic heterocyclic compounds, and organic acids and derivatives. Spearman correlation analysis revealed significant associations between Lachnospiraceae_unclassified and metabolites such as Gly-Leu, fumarate, and phenylpyruvic acid (|r| > 0.5, p < 0.05). Bioinformatics analysis suggested that TCYP may improve intestinal health by regulating key targets, including MMP9, TGFB1, and PPARG, as well as the peroxisome proliferator-activated receptor (PPAR) signaling pathway. Quantitative PCR (qPCR) results showed that, compared to the CON group, TCYP dose-dependently significantly upregulated the mRNA expression of PPARG, PDPK1, and Bcl2 in jejunal tissues (p < 0.05), while significantly downregulating the expression of MMP1 and Bax (p < 0.05).ConclusionTCYP enhances growth performance and intestinal health in broilers through multiple mechanisms, including maintaining cecal microbial homeostasis, modulating lipid and amino acid metabolism, with potential involvement of the PPAR signaling pathway based on bioinformatics and gene expression analysis.